Security of Biometric Data Using Compressed Watermarking Technique - Rohit Thanki; Komal Borisagar (Institute of Advanced Engineering and Science, 2014)
This paper has focus on biometric data security over open communication channel of biometric system. Here biometric data is encoded using cs theory and wavelet based embedding technique. The biometric data is convert into encoded sparse measurements which is generating using SVD, random seed and uniform quantization process. Then these encoded sparse measurements are embedding into the host color biometric data using wavelet based watermarking technique. This proposed technique has explored dimension reduction and computational security provided by compressive sensing. This proposed technique has also helps to compressed and to send secret data over noisy communication channel of biometric system against various attacks. The proposed technique provides more security compare to existed technique in literature due to CS theory. The novelty of proposed technique is that, watermark iris image information is compressed and encoded using CS theory and uniform quantization.DOI:http://dx.doi.org/10.11591/ijece.v4i5.6646